Spectrum of dermo-epidermic cutaneous gamma-delta lymphomas from a single center: clinical and phenotypic analysis of an heterogenous lymphoproliferative disorder. (October 2021) - Violetti, Silvia Alberti; Maronese, Carlo Alberto; Venegoni, Luigia; Sala, Emanuela; Berti, Emilio Francesco
Abstract : Primary cutaneous gamma delta T cell lymphomas (PCGDTCL) are a rare type of cutaneous lymphomas characterized by an heterogenous clinical and histological presentation which represents a huge challenge for diagnosis. Typically, PCGDTCL have a very bad prognosis, even if cases of cutaneous lymphomas with a gamma delta phenotype and an indolent course have been described. Based on these different reports, the last WHO classification divides PCGDTCL in epidermotropic, dermal and subcutaneous subtypes, leaving out cases with clinic and histologic features of classical mycosis fungoides and lymphomatoid papulosis. We evaluated dermo-epidermic cases of PCGDTCL from our center in Milan about clinic and phenotypic features. Nine patients were included: 2 patients with a pagetoid reticulosis-like PCGDTCL, 2 patients with peculiar pyoderma gangrenosus-like PCGDTCL and 5 patients with tumors and a previous history of MF. Neoplastic infiltrate was CD3 positive and double negative for CD4 and CD8 except for one case CD8+. Cytotoxic markers were present in all cases. Interestingly, we found that gamma-delta neoplastic cells were CD45RA positive and CD56 negative, a different expression compared the typical phenotype of subcutaneous forms. In the cases tested, the T cells expressed TCR Vd1, as expected. The subgroup of tumoral cases with a previous history of MF was the most peculiar. In these cases, the previous samples of MF had an atypical phenotype mainly CD4 positive and in two of them we could identify a partial expression of TCRdelta in the epidermotropic neoplastic cells, which probably represent a subclones. The selection of this subclones could represent the cause of the phenotypic switch in the aggressive PCGDTCL. More studies are needed to evidence the possible prognostic markers in MF cases which progressed in PCGDTCL.